1999
DOI: 10.1080/02772249909358699
|View full text |Cite
|
Sign up to set email alerts
|

Examination of mercury's effects during the process of the activated sludge

Abstract: The objectives of this report are: (a) the study of the mercury contaminated wastewater input effects at the activated sludge process in an activated sludge pilot plant and (b) the estimation of the removal ability of mercury's input, at different concentrations, from the activated sludge pilot plant.The concentration of inorganic mercury at the inlet of the plant varied from 0 to 100 µg/l HgCl 2 . The most important physical, chemical and biological parameters of the pilot plant were measured at least 4 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In a more detailed way, there was an increase in the concentration of the SS with a diameter larger than 122.87 mm and a respective decrease in the concentration of the smaller SS. This is an observation that is associated with the changes in the number and species of the bacteria in the aeration tank, before and after the introduction of mercury [1,19] and it probably indicates a possible way that microorganisms of the aeration tank react to the introduction of mercury. …”
Section: Discussionmentioning
confidence: 99%
“…In a more detailed way, there was an increase in the concentration of the SS with a diameter larger than 122.87 mm and a respective decrease in the concentration of the smaller SS. This is an observation that is associated with the changes in the number and species of the bacteria in the aeration tank, before and after the introduction of mercury [1,19] and it probably indicates a possible way that microorganisms of the aeration tank react to the introduction of mercury. …”
Section: Discussionmentioning
confidence: 99%
“…In an early study, Ghosh and Zugger (1973) reported that concentration of Hg(II) less than 2.5 mg l −1 had little effect on aerobic process, but aerobic processes were definitely inhibited at concentrations higher than 5 mg l −1 . Concentration of Hg(II) equal to 0.1 mg l −1 did not influence the removal of chemical oxygen demand (COD), but favored the generation of larger biological flocs (Pavlogeorgatos et al, 1999). In a follow-up study, Stasinakis et al (2003c) investigated the effect of Hg(II) and CH 3 Hg + on heterotrophic respiration rate of activated sludge microorganisms.…”
Section: Mercurymentioning
confidence: 99%
“…A pilot scale activated sludge wastewater treatment plant was constructed as described in detail by Pavlogeorgatos [12][13][14][15][16] (Figure 1). The operational parameters of the pilot plant are presented in Table 1.…”
Section: Experimental Setup and Samplingmentioning
confidence: 99%